Effect of Emulsion pH and Humectants on Sensory and Physico-Chemical Quality of Hurdle Treated Chicken Sausages - Karle, S.D.; Rindhe, S.N.; Suryawanshi, S.U.; Devangare, A.A.; Verma, S.K. (Journal of Meat Science, 2015)
The aim of this study was to develop acceptable quality of shelf stable chicken sausages using hurdle technology. Hurdles incorporated were humectants textured soya protein and low emulsion pH. Different parameters evaluated were pH, emulsion stability, cooking yield, moisture, protein, fat and sensory attributes. Incorporation of TSP at 4% level significantly (p<0.05) improved texture and overall palatability of chicken sausages, however, above 4% TSP level adversely affected different sensory attributes especially flavour. Addition of TSP was also significantly (p<0.05) improved emulsion stability, cooking yield, protein and fat content of chicken sausages. The acidulent used for reduction of emulsion pH was 0.5N lactic acid. Reduction of emulsion pH significantly (p<0.05) influenced the processing and quality parameters of chicken sausages. Emulsion pH below 5.70 adjusted with lactic acid affected different sensory attributes as well as physicochemical properties adversely. Findings of the study indicated that, acceptable quality hurdle treated chicken sausages could be prepared by incorporation of TSP at 4% with adjustment of pH at 5.70.